Zabawa dzieci z autyzmem w oddziaływaniach terapeutycznych – instrumentalna czy autoteliczna? - CHARBICKA, MAGDALENA (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Magdalena Charbicka, Zabawa dzieci z autyzmem w oddziaływaniach terapeutycznych – instrumentalna czy autoteliczna? [Play in autistic children in therapeuticwards – instrumental or autotelic?]. Interdyscyplinarne Konteksty PedagogikiSpecjalnej, nr 22, Poznań 2018. Pp. 105-125. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2018.22.06 Play is a typical and natural activity in children, which introduces it to the real world. It plays an uncommonly important function, thanks to the which the little person learns and gains information about their environment, the properties of objects, social relations or other rules. This area is different in children with autism. In most cases, play is accompanied by significant deficits, and the burden of focus of revalidation influences remains on the development of areas that are more disturbed, such as communication, disturbances in social interactions or behaviour hindering functioning. In course of therapeutic work, we sometimes forget the seemingly trivial activity that the playing of a child may be in view of adults. Considering this, it is worthwhile to take a look at the role ascribe to play by specialists over the years, and what it looks like in autistic children.